Cantilever flexural strength tests of masonry infill walls strengthened with textile-reinforced mortar. (January 2021) - Furtado, André; Rodrigues, Hugo; Arêde, António
Abstract: The main objective of this work is to present an experimental study on the use of textile reinforced mortar to improve the masonry infill walls out-of-plane behaviour. The experimental campaign comprises flexural strength tests parallel to the horizontal bed joints of 10 specimens made up of horizontal hollow clay bricks, five of them unstrengthened and the remaining five strengthened. Cantilever flexural strength tests were carried out. The efficiency of the strengthening was assessed and the effect of using a weak or strong textile mesh is analysed. The mechanical properties of the adopted materials are characterized and presented. The results are presented in terms of force-displacement responses and damages observed. From the tests, it was observed that the textile-reinforced mortars improved the flexural strength capacity until 3.93 times and the deformation capacity increased 2 times with a strong textile mesh. Highlights: Experimental study of using TRM to improve the masonry infill walls out-of-plane behaviour. 10 Cantilever flexural strength tests were carried out. TRM improved the flexural capacity until 3.93 times and the deformation until 2 times with a strong textile mesh.E